ANALISIS KOMPARATIF INDUSTI KREATIF E-COMMERCE: (Studi Kasus Pada JD.ID Dan Blibli.Com) - Dzikriyansah, Ahmad; Wiradika, M. Nur Hidayah; Hidayat, Dimas Taupik; Alexandri, Mohammad Benny; Hakim, Raden Marsha Aulia (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
Indonesia is a country that has projections in 2020 of e-commerce market growth that will continue to grow to reach US $ 20 billion. Therefore, the number of e-commerce sites that have sprung up in Indonesia with the aim of finding as many customers as possible. Blibli.com and JD.ID are examples of many e-commerce in the Indonesian market. E-commerce is one of the creative industries that is approved with the main weapons that rely on creativity and the support they have to utilize more resources. Therefore, this study was conducted to analyze the creative e-commerce industry with a comparative descriptive method to find the differences and streghts of each e-commerce. Key word: Creative Industries, E-commerce, Comparative Descriptive